THE PROCESSING TECHNIQUE AFFECTS THE PHYSICOCHEMICAL AND TEXTURAL CHARACTERISTICS OF PURPLE YAM BASED GLUTEN-FREE DOUGH - Ulyarti; Nazarudin; Lisani; Wulandari, Nur (Jurnal Teknologi Pertanian, 2024)
Purple yam tuber in the form of flour has been applied for functional food products. Processing purple yam tubers into flour eliminates many beneficial compounds of the tubers. Another alternative for processing purple yam tubers is to process them directly into a paste to be mixed into the dough. This study was carried out to determine the effect of the processing technique of yam tuber on the texture profile of gluten-free dough made up of yam tuber and modified cassava flour (mocaf). Four (4) types of processing techniques were applied to produce purple yam+mocaf dough. First (ST), steaming yam tuber, mashing + mocaf + water. Second (SST), steaming slice of yam tuber, mashing + mocaf + water. Third (SCT0.5), soaking slices of yam tuber in citric acid 0.5%, mashing + mocaf + yam tuber mucus. The last (SCT1) is soaking slices of yam tuber in citric acid 1%, mashing + mocaf + yam tuber mucus.  The result showed that the amount of water, the ratio between purple yam paste and mocaf, the lead time, and the processing technique play important roles in shaping the texture of the dough. The third technique (SCT0.5) produced higher hardness, adhesiveness, springiness, and cohesiveness dough than the other techniques. However, none of the texture profiles strongly correlate with the dietary fiber content. These results can be used better to understand the free gluten food application of yam tuber.